Analisis Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan perusahaan Rokok yang Listing Pada Bursa Efek Indonesia Periode Tahun 2009-2011 - Wulan, Tirza Ana (Jurnal Ilmiah Mahasiswa FEB, 2013)
Aims  of  this  study  was  to  examine  CSR  disclosure  influence  concerning  financial performance within  tobacco  companies  listed  on  Indonesian  Stock  Exchange.  This research  describes  the  influence  of  independent  variable  Corporate  Social Responsibility disclosure on  two dependent variables namely Return On Equity and stock  return.  This  research  included  in  the  type  of  explanatory  and  population research. This  research used 3  firms namely PT Gudang Garam Tbk., PT Hanjaya Mandala Sampoerna Tbk., and PT Bentoel  Internasional  Investama as a population for  a  period  of  3  years  from  2009-  2011.  This  research  used  linear  regression  to examine  Corporate  Social  Responsibility  disclosure  effect  to  tobacco  financial performance. The result couldn’t prove that both research hypothesis were Corporate Social  Responsibility  disclosure  have  positive  influence  to  Return  On  Equity  and stock  return.  It  means  that  investors  assess  the  Corporate  Social  Responsibility information  disclosed  by  the  companies  in  their  annual  reports  for  their  investment decision. Keywords : Corporate Social Responsibility, Return On Equity, Stock Return